THE INFLUENCE OF LEADERSHIP STYLE, TRAINING, ORGANIZATIONAL CLIMATE, ON EMPLOYEE PERFORMANCE AT PT SPECTRUM LINTAS SERVICE BATAM - Adelia Putri Indriani (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to determine the effect of leadership style, training, and organizational climate on employee performance at PT Spectrum Lintas Service. The research method used was a quantitative method with descriptive and associative approaches. The population in this study consisted of 100 employees, and a saturated sampling technique was applied so that all members of the population were used as research samples. Data were collected through questionnaires using a Likert scale and processed using IBM SPSS Statistics 25. The data analysis techniques included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). The results showed that leadership style had a positive and significant effect on employee performance with a t-value of 4.185 and a significance value of 0.000. Training had a positive and significant effect on employee performance with a t-value of 2.763 and a significance value of 0.007. Organizational climate also had a positive and significant effect on employee performance with a t-value of 6.422 and a significance value of 0.000. Simultaneously, leadership style, training, and organizational climate had a significant effect on employee performance with an Fvalue of 158.059 and a significance value of 0.000. The coefficient of determination (R²) value of 0.832 indicated that 83.2% of employee performance was influenced by leadership style, training, and organizational climate.